REFORMASI BIROKRASI ADMINISTRASI PELAYANAN PAJAK KENDARAAN BERMOTOR BERBASIS MOBILE TECHNOLOGY DI KANTOR BERSAMA SAMSAT PROVINSI JAWA TIMUR - Sunarya, Aris (JPAP: Jurnal Penelitian Administrasi Publik, 2016)
This study aims to analyze and understand the urgency the development of bureaucracy reform as one of the regional taxation service administration reform comprises of policies regulation element, human resources, information technology and coordination to resulting in public service is clearly its benchmark toward data efficiency and effectiveness improvement of governance and procedures in KB Samsat and also increasing transparency and accountability, so simultaneous commitment of the action to determine the successful of bureaucracy reforms implementation. Bureaucracy reforms of regional taxation service administration in KB Samsat with mobile technology to answer the service development challenges already done by KB Samsat of East Java and the developing of tax service administration on motor vehicles is paperless-based or further development. These development done sustainable from human resource, institutional and visionary leadership by creating Samsat service fall into 2 lockets with Conventional Samsat, Semi Modern Samsat and Modern Samsat models with cooperation Government to Government (G to G), Goverment to Bussines (G to B), Goverment to Citizen (G to C) by benefitting optimum information technology toward mobile technology then emerge service product and report administration suitable with people’s expectation today.Keywords : Bureaucratic Reform, Public Service Innovation, Tax Administation Reform, Mobile Technology.